Factors influencing teacher performance in Shanghai high schools in COVID-19 pandemic - Jiang, Yuan; Yusof, Mat Rahimi; Kasa, Muhamad Dzahir (Institute of Advanced Engineering and Science, 2025)
The performance of teachers in schools has become a questionable phenomenon during COVID-19 due to changing landscape of teaching. Since the performance of teachers is linked to performance of students, it is imperative to investigate the influencing factors for teachers’ performance. This study is conducted to examine the relationships between instructional leadership (IL), teaching autonomy (TA), school resources (SR), teacher self-efficacy (TSE), teacher performance (TP) and teaching workload (TW). A sample of 321 responses was collected using a Likert scale questionnaire. Partial least square–structural equation modeling (PLS-SEM) was used to analyze the data using Smart PLS 3. The findings of the study confirmed that TA, IL, and SR are significant antecedents of TSE. The study reports that TSE is a significant predictor of TP. The study reports that TSE is a significant mediator and TW is a significant moderator. The study suggests that TP can be improved with TSE which is improved by IL, TA, and SR. The school education administration in China is required to develop policies in line with this research to contribute to knowledge. The study recommends that the policymakers and practitioners should focus on school’s resources, IL and TA which significantly will improve the performance of teachers in China.